BIAL 16(1), 2006 página 24 - POLI NETO, Adelino; MATOS, Dulcilena de; GOMES, Áquila Maria Lourenço; FERREIRA, Antonio Roberto de Souza; PARDI, Paulo Celso; CERQUEIRA, Esem Pereira (Boletim do Instituto Adolfo Lutz - BIAL, 2006)
Adelino POLI NETO1, Dulcilena de MATOS1, Áquila Maria Lourenço GOMES1, Antonio Roberto de Souza FERREIRA1, Paulo Celso PARDI2, Esem Pereira CERQUEIRA3 1Instituto Adolfo Lutz 2Universidade Bandeirante 3Museu de Anatomia Humana Prof. Alfonso Bovero – USP